Slowing Down to Feel: Artistic Appreciation at the Heart of Secondary Arts Education (Revista de Ensino em Artes, Moda e Design, 2025)
The author has taught visual arts in a Montreal secondary school for over 15 years, a practice enriched by sociocultural shifts and tailored to students’ needs, rooted in the present and aimed at their future. Captivated by contemporary and socially engaged art, she has gradually centered her pedagogy on aesthetic appreciation, a tool to connect teenagers to their environment in a world shaped by social crises and digital ubiquity. Facing school constraints—strict schedules, large classes, sensitive discussions—she adapted her methods, prioritizing reflection by easing the pace of lessons. The pandemic heightened these challenges while unveiling art’s transformative power. Since then, she has emphasized contemporary artistic appreciation, weaving technologies into innovative pedagogical projects. Drawing on music, animation, and interculturality, and inspired by local and Canadian artists, she engages students in exploring diversity and current issues, strengthening their sense of belonging. For her, artistic appreciation, both an act of resistance and connection, fosters an inclusive, meaningful education, resonating with the aspirations of youth navigating a complex world.
Keywords: artistic appreciation; challenges; technology; adolescent; multiculturalism